Motorization vs. pedestrianization: an analysis of user perception in the historic center of Toluca (2024)
Motorization in large cities currently constitutes a factor that demands alternatives for urban centres to recover their functionality and offer their inhabitants public spaces that prioritize social interaction. The objective of this article is to analyse the perception of the population that for some reason goes to the historic centre of the city of Toluca, Mexico, regarding its pedestrianization. For this purpose, a semi-structured survey was designed that collects the opinions of visitors to this polygon, considering the reasons for travel, costs, modes of transportation and their position in Favor of or against pedestrianization. The results indicate that, although there is a high percentage (69%) that supports initiatives to avoid traffic congestion and implement improvement actions, it is also a reality that pedestrianization cannot be total: 53.5% of the population is in favour of partially pedestrianizing, that is, only some roads, while 31% prefer to maintain the conditions as they currently are despite the negative effects that prevail. These figures reflect that the authorities responsible for urban mobility at the local and state level must take on the challenge of designing alternatives to move towards more sustainable schemes that counteract the externalities derived from the increase in the motorization rate in the historic centre of Toluca.